Barriers to breast cancer screening in Iranian females: a review article - Masoudi, Nazanin; Dastgiri , Saeed; Sanaat, Zohreh; Abbasi, Zhila; Dolatkhah, Roya (Faculty of Medicine, Universitas Trisakti, 2022)
Breast cancer is one of the most common malignancies among females in Iran. Screening and detection in the early stages can increase the likelihood of breast cancer treatment and prognosis, thereby decreasing the mortality rate and promoting patient survival. However, mass screening programs for breast cancer are still confronted by predominant barriers in Iran. We tried to review and recognize the barriers to breast cancer screening and early detection in Iranian females as the main research question. We searched all available databases, and screened manuscripts for eligibility according to our inclusion/exclusion criteria. The search strategy was based on the following keywords: Breast, Malignancy, Cancer, Screening, Early Detection, Mammography, Iran, and Barrier. Responsible authors performed a literature review and compiled the results into a report. Various perceived barriers at different levels (individual, intrapersonal, health systems, and community) play influential and pivotal roles in women’s decisions to participate in breast cancer screening programs to facilitate early detection. Lack of awareness, neglect, procrastination, embarrassment, religious beliefs, and lack of primary health workers awareness and recommendation were cited as perceived barriers in screening procedures in Iran. There are still barriers in performing mammography at population levels in five major dimensions including availability, accessibility, cost, fears, and acceptability. However, the rate of regular mammography utilization in Iran is low compared with other countries and needs increasing through informing women. Many perceived barriers can affect women’s willingness and self-efficacy in screening procedures and one of the most effective ways of overcoming these barriers is to increase women’s awareness.